How can we learn to learn? (Docentes 2.0 Journal, 2016)
Actually, there is no magic formula in the learning process, because we don't all learn the same. But if we can give you some advice that where they are intended to teach you to schedule your study time, to organize your study material, to use the resources and services available through libraries, to read and take notes correctly, to summarize and memorize what learned.
Keywords: How can; learn to learn